2014
DOI: 10.1021/jo500634d
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Bicyclic γ-Silyloxy-β-hydroxy-α-diazolactones as an Approach to Ynolides

Abstract: Medium-sized ynolides were prepared by the Lewis acid-mediated fragmentation of bicyclic γ-silyloxy-β-hydroxy-α-diazolactones in which the Cβ–Cγ bond is the ring fusion bond. Although these lactone fragmentation substrates reacted somewhat less efficiently than their carbocyclic counterparts, the fragmentation provided 11-membered ynolides in up to 84% yield. Unlike prior fragmentations of similar substrates, elevated temperatures were required to obtain optimum yields of the ynolide products. The ynolides rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Although vinyl cations have been studied for over 60 years, a lack of methods to generate these highly reactive intermediates has hindered the development of general, synthetically useful reactions. , However, the recent realization of milder ways to form vinyl cations has led to renewed interest in their reactivity. For example, our group has taken advantage of vinyl cations to develop a ring fragmentation reaction, as well as methods to form cyclopentenones , and indenones (Scheme ). These reactions take advantage of Padwa and Pellicciari’s finding that vinyl cations are formed when β-hydroxy-α-diazo carbonyl compounds are treated with a Lewis acid .…”
Section: Introductionmentioning
confidence: 99%
“…Although vinyl cations have been studied for over 60 years, a lack of methods to generate these highly reactive intermediates has hindered the development of general, synthetically useful reactions. , However, the recent realization of milder ways to form vinyl cations has led to renewed interest in their reactivity. For example, our group has taken advantage of vinyl cations to develop a ring fragmentation reaction, as well as methods to form cyclopentenones , and indenones (Scheme ). These reactions take advantage of Padwa and Pellicciari’s finding that vinyl cations are formed when β-hydroxy-α-diazo carbonyl compounds are treated with a Lewis acid .…”
Section: Introductionmentioning
confidence: 99%
“…2 ). 21 24 In that reaction, a vinyl cation, 25 , 26 formed from the diazo alcohol by the process described by Pellicciari 27 and Padwa, 28 underwent a Grob-type fragmentation that was facilitated by the γ-silyloxy group. We hypothesized that a β-hydroxy-α-diazo ketone that lacks a fragmentation-promoting group at the γ position might instead react by a C–H insertion pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Later, it was shown that various α-diazo-γ-butyrolactones can be synthesized in direct diazo transfer conditions at low temperatures. However, this method did not gain popularity because of the formation of large numbers of triazine and azide side-products [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Much better results were achieved using detrifluoroacetylating diazo transfer, which to-date is the most widely accepted method of synthesizing α-diazo lactones, including six- and seven-membered ones ( Scheme 73 ) [ 5 , 96 , 109 , 110 ].…”
Section: α-Diazo Lactonesmentioning
confidence: 99%
“…Unfortunately, for lactones, this transformation is much less effective than for ketones. Similar to ketones, macrocyclic products are obtained with better yields from cis-bicyclic lactones compared to their trans-counterparts ( Scheme 79 ) [ 118 ].…”
Section: α-Diazo Lactonesmentioning
confidence: 99%